Formation of a regular neo-epidermis by cultured human outer root sheath cells grafted on nude mice - Limat, Alain; Breitkreutz, Dirk; Thiekoetter, Gabi; Klein, C. Eberhard; Braathen, Lasse R.; Hunziker, Thomas; Fusenig, Norbert (Transplantation, 1995)
The outer root sheath of hair follicles mainly consists of basal-like keratinocytes which can substitute for interfollicular epidermal keratinocytes, as during healing of skin wounds when outer root sheath cells migrate onto the denuded area, thus contributing to epidermal regeneration. Human outer root sheath cells represent a repeatedly available source of keratinocytes which can be easily and extensively expanded in culture. - Close comparison of organotypic cultures of either outer root sheath cells or epidermal keratinocytes grafted onto nude mice demonstrated that outer root sheath cells formed a stratified epithelium resembling normal epidermis that is virtually indistinguishable from that developed by epidermal keratinocytes. Typical epidermal differentiation markers, such as the suprabasal keratins 1 and 10, involucrin, filaggrin, the basement membrane components collagen type IV and laminin, and the integrin chains α2, α3, α6, and β1, were readily expressed in a mostly regular localization.. - These data suggest that outer root sheath cells, bearing essential advantages as compared with interfollicular keratinocytes, are suitable for skin replacement.
Gesehen am 27.02.2025